2016
DOI: 10.4236/pp.2016.73015
|View full text |Cite
|
Sign up to set email alerts
|

Middle Molecular Weight Heparinyl Amino Acid Derivatives (MHADs) Function as Indirect Radical Scavengers <i>in Vitro</i>

Abstract: We conducted the novel synthesis of middle molecular weight heparinyl amino acid derivatives (MHADs) to reduce the adverse effect of heparin (HE) based on its anticoagulant activity. Subsequently, we investigated the radical scavenging effects of 12 kinds of MHAD on cultured human umbilical vein endothelial cells (HUV-ECs) damaged by oxygen free radicals using xanthine and xanthine oxidase in vitro. As a result, middle molecular weight heparinyl phenylalanine, middle molecular weight heparinyl leucine, and mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We have synthesized and studied a novel medium molecular weight HE (MHE) and its amino acid derivatives (MHADs), in which eleven kinds of amino acids were adducted to MHE to develop safe and effective heparin derivatives. We found that some MHADs had a function as indirect radical scavengers (1)(2)(3). In this paper, we examined the inhibitory action of MHADs on scorpion venom (SV)-induced acute pulmonary edema.…”
mentioning
confidence: 99%
“…We have synthesized and studied a novel medium molecular weight HE (MHE) and its amino acid derivatives (MHADs), in which eleven kinds of amino acids were adducted to MHE to develop safe and effective heparin derivatives. We found that some MHADs had a function as indirect radical scavengers (1)(2)(3). In this paper, we examined the inhibitory action of MHADs on scorpion venom (SV)-induced acute pulmonary edema.…”
mentioning
confidence: 99%
“…We previously synthesized twelve novel medium molecular weight heparinyl amino acid derivatives (MHADs) to reduce the anticoagulant activity of HE and investigated their beneficial pharmacological activity. Among them, medium molecular weight heparinyl phenylalanine (MHF), medium molecular weight heparinyl leucine (MHL), and medium molecular weight heparinyl tyrosine (MHY) functioned as indirect radical scavengers in vitro (4). MHF and MHL were superior to HE as safe radical scavengers in vivo.…”
mentioning
confidence: 99%
“…MHF and MHL are superior to heparin (HE) as safe radical scavengers (1,2). However, the mechanism of MHF and MHL as radical scavengers is unknown.…”
mentioning
confidence: 99%